1996
DOI: 10.1002/(sici)1097-4628(19960418)60:3<379::aid-app11>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interfacial FTIR spectroscopic studies of latexes. XII. Particle size effect and surfactant behavior in electrodeposited Sty/n-BA latex films

Abstract: Polarized attenuated total reflection Fourier transform infrared spectroscopy was used to assess the mobility and orientation of sodium dioctylsulfosuccinate surfactant molecules at the film–air (F–A) and film–substrate (F–S) interfaces in electrodeposited latex films. Copolymer compositions ranging from 100% poly(n–BA) to 50%/50% Sty/n–BA were examined. When particle diameters are 50 and 100 nm, it appears that the 1046 cm−1 band is detected at the F–A and F–S interfaces. However, the 1056 cm−1 band is detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] Thus, continuous quests for advancing our knowledge continue by exploring new avenues. For example, it has not been realized until recently that their synthesis may be facilitated by amphiphilic bioactive molecules, such as phospholipids, 13,14 and this approach opened up new scientific and application avenues of polymeric colloidal dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Thus, continuous quests for advancing our knowledge continue by exploring new avenues. For example, it has not been realized until recently that their synthesis may be facilitated by amphiphilic bioactive molecules, such as phospholipids, 13,14 and this approach opened up new scientific and application avenues of polymeric colloidal dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…A series of the previous studies on latex films indicated that the mobility of low molecular weight species, in particular surfactant molecules, may be affected by latex glass transition temperature (T g ), which is inherently related to the free volume of a polymer matrix, 3,4 surface tension at the film-air (F-A) and film-substrate (F-S) interfaces, [5][6][7][8][9][10] compatibility of individual components, [11][12][13][14][15][16][17][18] and coalescence times. [18][19][20] It turns out that there are other factors that influence the distribution of individual components across the latex film, and interactions among them become increasingly important during the film formation. Although, for typical copolymer latexes with T g below the minimum film-formation temperature (MFT), continuous-phase morphology is believed to be affected by the particle packing and subsequent particle deformation followed by interparticle diffusion and film formation.…”
Section: Introductionmentioning
confidence: 99%
“…Transient Effects during Coalescence. Although we addressed the issue of mobility and stratification of individual components in latexes in a number of previous studies, their relevance becomes even more pronounced in the context of latex films examined in this paper. In essence, the real question is, can surfactants be seen at various coalescence stages, and if so, how are surface interfacial properties affected?…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on thermoplastic latex films indicated that mobility of low molecular weight anionic surfactants may be affected by latex glass transition temperature (T g ), and subsequently, free volume of a polymer matrix, 6,7 surface tension at the film-air (F-A) and film-substrate (F-S) interfaces, [8][9][10][11][12][13] compatibility, [14][15][16][17][18][19][20][21][22] coalescence times, [14][15][16][17][18][19][20][21][22][23][24] and latex particle structures. 25,26 In view of the above considerations, surfactant behavior in thermosetting type latex film formation processes has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation